The Arson of a Museum: Ethnography of historical experience and plant fiber use in northern Coclé Province, Panama - Müller-Schwarze, Nina K. (Ethnobotany Research and Applications, 2015)
The use of tree cambium to make cucua dance outfits attracted the attention of international plant and culture conservationists. Scholarly narratives, media interpretations, and publications for the tourism market about cucua often reiterate racialized colonial categories as the origin point for a history construed as Panamanian. Implementation of conservation programs, like the construction of a museum and cultural center, ignored existing social structures among dancers. Arsonists allegedly destroyed the museum. This article presents data collected in anthropological participant observation methodologies and describes why conservation programs were rejected through the ethnography of historical experience that shows how people make sense of the past. Local explanations of plant uses that include power accessed through the ruptures of social structures during liminal times, such as Spanish colonialism, are real and not just symbolic. This article places cucua plant use in cultural context with other plant fibers used in northern Coclé for baskets, all called “weaving.”